2010
DOI: 10.2337/db10-0276
|View full text |Cite
|
Sign up to set email alerts
|

Lack of TRPM2 Impaired Insulin Secretion and Glucose Metabolisms in Mice

Abstract: OBJECTIVETRPM2 is a Ca2+-permeable nonselective cation channel activated by adenosine dinucleotides. We previously demonstrated that TRPM2 is activated by coapplication of heat and intracellular cyclic adenosine 5′-diphosphoribose, which has been suggested to be involved in intracellular Ca2+ increase in immunocytes and pancreatic β-cells. To clarify the involvement of TRPM2 in insulin secretion, we analyzed TRPM2 knockout (TRPM2-KO) mice.RESEARCH DESIGN AND METHODSOral and intraperitoneal glucose tolerance te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(143 citation statements)
references
References 28 publications
7
136
0
Order By: Relevance
“…Uchida et al [15] reported that TRPM2 knockout mice exhibit slightly elevated basal insulin, impaired glucose tolerance, but normal fasting blood glucose levels. Zhang et al [17], by contrast, reported that TRPM2 knockout improves glucose tolerance (due to improved insulin sensitivity), but has no effect on basal glucose or insulin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uchida et al [15] reported that TRPM2 knockout mice exhibit slightly elevated basal insulin, impaired glucose tolerance, but normal fasting blood glucose levels. Zhang et al [17], by contrast, reported that TRPM2 knockout improves glucose tolerance (due to improved insulin sensitivity), but has no effect on basal glucose or insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation thus can raise cytosolic Ca 2 + through extracellular entry and lysosomal release. The TRPM2 channel is proposed to play a dual role in β-cell physiology with modest TRPM2-mediated Ca 2 + elevation being implicated in glucose-stimulated insulin secretion [15,16], although the in vivo evidence in TRPM2-knockout mice is somewhat controversial [15,17]. However, strong activation of the channel causes excessive Ca 2 + elevation resulting in β-cell death [9,11,12,14,18].…”
Section: Introductionmentioning
confidence: 99%
“…These agonists are believed to act on a unique C-terminal pyrophosphatase domain in TRPM2 (Nudix-like domain) (11)(12)(13). Temperature-dependent activation of TRPM2 plays significant roles in cellular functions, including insulin release from pancreatic β cells (10,14). TRPM2 channels can be activated by hydrogen peroxide (H 2 O 2 ) and are reported to be involved in cell death caused by oxidative stress via mechanisms that remain to be clarified (15,16).…”
Section: Calcium | Immune Cellsmentioning
confidence: 99%
“…On contact with pathogens, phagocytic cells produce reactive oxygen species (ROS); the resulting activation of TRPM2 provides the Ca 2+ influx necessary for cell migration and chemokine production (1). In pancreatic β cells, TRPM2 activity contributes to glucose-evoked insulin secretion; TRPM2 knock-out mice show higher resting blood glucose levels and impaired glucose tolerance (2).…”
mentioning
confidence: 99%